Автоматизовані засоби тестування програмних модулів розв’язування інтегральних рівнянь Вольтерри другого роду - Іванюк, Віталій; Мястковська, Марина; Понеділок, Вадим (Kamianets-Podilskyi National Ivan Ohiienko University, 2023)
The article is part of the methodology of automated testing of software modules for solving Volterra integral levels of the second kind. For the implementation of automated testing, the Matlab software environment was selected, which has a wide range of software testing capabilities, in particular: functions for generating data sets for testing; functions for comparing test results; functions for generating test reports, etc. For the development of automated testing tools, the Unit Testing Framework was selected, which is a component of the MATLAB Test Framework, has many ready-made methods for checking the correctness of values and the formation of statistical errors. A set of test problems has been developed for Volterra integral equations of the second kind, which are divided into different types, including linear Volterra integral equations of the second kind, which consist of a kernel with power, exponential, hyperbolic, logarithmic, trigonometric, inverse trigonometric functions and their combination. Developed testing tools used for automated quality control of software modules built on the basis of left rectangle, right rectangle, trapezoidal, and Simpson methods. The developed set of test tasks covers a wide range of possible operating conditions of software modules. The results of the testing allowed to improve the existing software modules to achieve the set conditions for their operation. The conducted research should contribute to the development of more reliable and efficient software modules for solving Volterra integral levels of the second kind. The obtained results are the basis for further research, which will be used in the following directions: development of testing methods for more complex types of Volterra integral levels of the second kind, including the level with nonlinear and non-stationary kernels.